Integrating a Far‐Red Fluorescent Probe with a Microfluidic Platform for Super‐Resolution Imaging of Live Erythrocyte Membrane Dynamics. (12th October 2022) - Ye, Zhiwei; Yang, Wei; Zheng, Ying; Wang, Shujing; Zhang, Xiaodong; Yu, Haibo; Li, Shuangshuang; Luo, Chunxiong; Peng, Xiaojun; Xiao, Yi
Abstract: Living erythrocyte (red blood cell, RBC) membranes present rich ultrastructural and dynamic details, which require synchronous super‐resolution imaging and single‐molecule tracking to be revealed. Yet, it poses a serious challenge to achieve these dual functions in a single probe, due to the rigid and conflicting photophysical demands of the different techniques. Herein, we rationally developed a far‐red boron dipyrromethene membrane probe with blinking capability and persistent single‐molecule emission, and constructed a microfluidic platform for noninvasive trapping and long‐term imaging of RBCs. By combining them, multi‐dimensional super‐resolution reconstructions and single‐molecule tracking were achieved at the molecular scale on living human RBC membranes in a high‐throughput manner. Our integrated system defines a quantitative method for analyzing RBC membranes under physiological and pathological conditions, improving precision and revealing new perspectives for future disease diagnostics. Abstract : A far‐red fluorescent probe with blinking and lasting emission is developed to meet the contradictory requirements of super‐resolution imaging and single‐molecule tracking. A microfluidic device is fabricated to trap red blood cells (RBCs) and to enable the manipulation of the microenvironment. The integration of the probe and device has uncovered nanoscale dynamics of living RBC membranes, providing a means to advance diagnostics to the molecular level.